PENERAPAN MODEL PEMBELAJARAN KOOPERATIF PENDEKATAN THINK PAIR SHARE (TPS) UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA SISWA KELAS X4 SMA NEGERI 9 PEKANBARU - Ruri Septika; Zulkarnain '; Rini Dian Anggraini (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Absract: This research aims to improve the learning process and improve learning result in mathematics at SMA Negeri 9 Pekanbaru by applying the model of Cooperative Learning Think Pair Share (TPS). This research is a class action research by two cycles. Each cycle has four phases, they were planning, implementation, observation and reflection. Subjects were class X4 students consist of 16 boys and 24 girls who have academic ability is heterogeneous. The research instrument consists of learning devices and instrument data collectors. Learning device used in this research is Syllabus, Lesson Plan, and Worksheet. The instrument data collector used in this research is the observation sheet and math achievement test. The data analysis technique utilized qualitative and quantitative data analysis technique. Based on the result of the research showed that the learning process had performed well after has been made. An increase in the number of students who received grades of 20 and 30 as many as 27 students on first cycle and 32 students on second cycle. That is also an increase in the number of students who achieve at KKM end of UH each cycle compared to the number of students who achieve a score of KKM on the base. Starting from 27,5% increase to 35% and increased to 72,5%. The development of the results of this research indicate that the application of the Cooperative Learning Think Pair Share (TPS) can improve the learning process and improve learning results class X4 junior high school math class students Negeri 9 Pekanbaru in the academic year 2015/2016 at Basic Competencies (1) Menyelesaikan sistem persamaan  linear dan sistem persamaan campuran linear dan kuadrat dalam dua variabel, (2) Merancang model matematika dari masalah yang berkaitan dengan sistem persamaan linear, dan (3) Menyelesaikan model matematika dari masalah yang berkaitan dengan sistem persamaan linear dan penafsirannya.. Key Words: Mathematics Learning Result, Learning Process, Cooperative Learning, Think Pair Share, Classroom Action Research